Global Training And Development - Soetjipto, Budi W. (Forum Manajemen; Vol 10 No 63 (1996): Forum Manajemen Prasetiya Mulya| Proses Integrasi Global Makin Membutuhkan Langkah-Langkah Terencana, 1996)
Nowadays there is almost no firm can avoid global competition. This kind of competition is different from regional or local/domestic competition. Nevertheless, the key success factor stays the same that is having the competitive advantage. Unfortunately, the traditional sources of competitive advantage are no longer powerful in global competition which means they will not be able to create the competitive advantage needed to win the competition. Hence, we need to develop a new source of competitive advantage beyond the traditional ones. The most potential candidate for a new source of competitive advantage is human resource. In order to be a powerful source of competitive advantage, human resource has to be capable, and being capable, human resource needs to be trained and developed. This article will try to describe tlie training and development practice under the global competition environment which includes the definition, objectives, effective management of such practice, alternative methods, and alternative approaches for designing the global training and development · programs. In addition, it will describe the specific training and development practice for parent country national, third country national-and home.country national employees. At the end part of the article, there_ will be one global training and development practices _case study of a U.S. based company.